1991
DOI: 10.1128/mr.55.4.561-585.1991
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress responses in Escherichia coli and Salmonella typhimurium

Abstract: Oxidative stress is strongly implicated in a number of diseases, such as rheumatoid arthritis, inflammatory bowel disorders, and atherosclerosis, and its emerging as one of the most important causative agents of mutagenesis, tumorigenesis, and aging. Recent progress on the genetics and molecular biology of the cellular responses to oxidative stress, primarily in Escherichia coli and Salmonella typhimurium, is summarized. Bacteria respond to oxidative stress by invoking two distinct stress responses, the peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 686 publications
(121 citation statements)
references
References 241 publications
2
116
0
3
Order By: Relevance
“…This reduction could potentially be catalysed by two proteins encoding typical 2-Cys subfamily peroxiredoxins (GSU0352 and GSU3246) and glutaredoxin (GSU1155), which were more highly expressed in cells grown in the presence of U(VI) (Table 2). Homologues of rhodanese-like proteins (GSU0505 and GSU2516) that are involved in the oxidative stress response of E. coli (Farr & Kogoma, 1991) were also expressed in higher abundance when U(VI) was present (Table 2).…”
Section: Proteins Involved In Oxidative Stressmentioning
confidence: 99%
“…This reduction could potentially be catalysed by two proteins encoding typical 2-Cys subfamily peroxiredoxins (GSU0352 and GSU3246) and glutaredoxin (GSU1155), which were more highly expressed in cells grown in the presence of U(VI) (Table 2). Homologues of rhodanese-like proteins (GSU0505 and GSU2516) that are involved in the oxidative stress response of E. coli (Farr & Kogoma, 1991) were also expressed in higher abundance when U(VI) was present (Table 2).…”
Section: Proteins Involved In Oxidative Stressmentioning
confidence: 99%
“…A gene for the gamma-subunit of exodeoxyribonuclease V (ACP86_09165), also known as RecD, was also more highly expressed. In E. coli , RecBCD initiates recombinatorial repair of damaged double-stranded DNA, including that caused by oxidative stress [ 45 ]. The genes for the alpha- and beta-subunits, RecBC (ACP86_09155 and ACP86_09160) were not differentially expressed at the cutoff values.…”
Section: Resultsmentioning
confidence: 99%
“…These results all indicated that after exposure to NaClO, a strong oxidative stress reaction occurred in E. coli, which caused its oxidative injury and formed disinfectantinjured bacteria ( Jin et al 2020). Studies have shown that oxidative stress can lead to the peroxidation of lipids on bacterial cell membranes, which will destroy the structural integrity of the cell membrane and affect the related functions of the membrane (Farr & Kogoma 1991;Ibrahim et al 2000). Tandon et al (2007) found that chlorine-injured E. coli and Enterococcus faecalis become sensitive to ROS, giving higher counts under ROS-neutralized enumeration conditions than under conventional aerobic conditions.…”
Section: The Injury Mechanism Of E Coli In Response To Chlorine Disinfectionmentioning
confidence: 91%